Assistive technology, information asymmetry and the role of brokerage services: a scoping review - Lynne Pezzullo; Nathan Martin D'Cunha; Stephen Isbel; Nenad Naumovski; Diane Gibson; John Goss (BMJ Open)
Objectives Access to assistive technologies (ATs) is a human right for people with disabilities, but there are a range of barriers, including lack of adequate information. This review aimed to explore the implications of information asymmetry on the delivery of AT and to investigate if there are effective and equitable ways of providing AT brokerage services to people needing AT.Design Scoping review.Data sources EBSCO Medline, EBSCO Cinahl, Academic Search Ultimate, Business Source Ultimate, Proquest Central, Scopus, Web of Science, PsychINFO, EconLit and JSTOR were searched through 18 July 2021.Eligibility criteria Intervention and observational studies and articles directly related to information asymmetry and brokerage in the context of AT were included. In addition, a scan of web-based resources and services was undertaken.Data extraction and synthesis Four authors independently screened the articles for inclusion and performed a narrative synthesis.Results Thirty-three articles were identified. The narrative synthesis showed that: (1) AT users want access to impartial information sources; (2) users want to be involved in AT selection; (3) users benefit from access to demonstration sites; (4) users want access to training and ongoing support in their use of AT; and (5) users want access to information on new and emerging technologies. Access to information and user engagement, we produced better outcomes and satisfaction. Web-based repositories are valuable for user research and peer feedback, while demonstration sites address the need for expert advice, trial use of equipment, training and support in equipment use and maintenance.Conclusions Access to impartial information brokerage is critical to optimise AT selection. The implications of information asymmetry include lower user satisfaction, equipment underutilisation or abandonment. Aspects such as access to demonstration sites and web-based resources were also important.